Tapioca Starch is used as An Adhesive in "Complete Feed Wafers" Based on Fermented Sugarcane Tops and Tithonia for the Physical Properties of Wafers - Ikhlas, Zaitul; Jamarun, Novirman; Zain, Mardiati; Agustin, Fauzia; Yanti, Gusri; Fitri, Yelly; Safitri, Rika; Hidayat, Muhammad Zhorif (Andalasian Livestock, 2024)
This study aims to determine how long fermented sugarcane tops (Saccharum officinarum L.) and tithonia (Tithonia diversifolia) wafers can be stored. This study used a completely randomized design with four treatments and four replicates. The treatments consisted of T1 (15 days storage duration), T2 (30 days storage duration), T3 (45 days storage duration), and T4 (60 days storage duration). The variables measured were color, aroma, texture, density, water absorption, and total fungal colonies. The data obtained from the study were analyzed using the variance analysis method, and the differences in the means of each treatment were further tested using the Duncan Multiple Range Test. The results of the analysis showed that shelf life had a very significant effect (P<0.01) on color, aroma, texture, water absorption, and total fungal colonies but gave no significant effect (P>0.05) on wafer density. The average results of color (3.3 - 3.7), aroma (3.2 - 3.6), texture (3.1 - 3.6), density (0.60 - 0.71 g/cm3), water absorption (72.8 - 85.3%) and total fungal colonies (1.10 x 102 CFU/ml to 3.03 x 102 CFU/ml). The results of this study indicate that 60 days of storage on sugarcane tops and tithonia wafers can still maintain the physical quality of wafers in terms of color, aroma, texture, water absorption, and total fungal colonies.